Low Molecular Weight Heparin versus Warfarin in the Prevention of Recurrences after Deep Vein Thrombosis - Pini, M; Aiello, S; Manotti, C; Pattacini, C; Quintavalla, R; Poli, T; Tagliaferri, A; Dettoi, A G (Thrombosis and Haemostasis, 1994)
To evaluate the role of low-molecular weight heparin (LMWH) as an alternative to oral anticoagulants in the prevention of recurrent venous thromboembolism, we compared in a randomized trial conventional warfarin treatment with a three-month course of enoxaparin 4000 anti-Xa units once a day subcutaneously. 187 patients with symptomatic deep-vein thrombosis (DVT), diagnosed by strain-gauge plethysmography plus D-dimer latex assay and confirmed by venography in most cases, were treated with full-dose subcutaneous heparin for ten days and then randomized to secondary prophylaxis. During the 3-month treatment period, 6 of the 93 patients who received LMWH (6%) and 4 of the 94 patients on warfarin (4%) had symptomatic recurrence of venous thromboembolism confirmed by objective testing (p = 0.5; 95% confidence interval [Cl] for the difference, -3% to 7%). Four patients in the LMWH group had bleeding complications as compared with 12 in the warfarin group (p = 0.04; 95% Cl for the difference, 4% to 14%). In the 9-month follow-up period, during which 34 patients on warfarin prolonged treatment for other 3 months and 14 up to one year, 10 patients in the enoxaparin group and 4 patients in the warfarin group suffered a documented recurrence of venous thromboembolism. Of these 14 late recurrences, just one occurred in patients with postoperative DVT. After one year there were 16 recurrences (17%) in the LMWH group and 8 (9%) in the warfarin group (p = 0.07; 95% Cl for the difference, 1% to 16%).These results confirm the potential of LMWH as an alternative to oral anticoagulants in this setting, and suggest to evaluate in a prospective study a slightly higher dose of enoxaparin in patients with postoperative DVT.